DESKRIPSI PROSES KEPUTUSAN PEMBELIAN SAYURAN ORGANIK YANG DILAKUKAN OLEH KONSUMEN WARUNG SEHAT 1000 KEBUN BANDUNG - Tasya Maulida Hermansyah; Kuswarini Kusno (Universitas Galuh, 2022)
The trend of consumption of organic vegetables in urban areas is increasing. Warung Sehat 1000 Kebun Bandung is one of the organic vegetable marketers in Bandung. The number of competitors and ensuring the availability of organic vegetables according to consumer needs is a problem that is being faced. This study aims to describe consumer characteristics, purchase decision processes, and analyze the factors that influence consumer purchasing decisions. This study applies a quantitative design with a survey technique to 42 respondents. Sampling was done by convenience. Data were analyzed by frequency distribution to determine the description of consumer characteristics, purchasing decision processes, and factors that influence consumer purchasing decisions. Based on the research results, consumers of organic vegetables at Warung Sehat 1000 Kebun Bandung are mostly women aged 36-45 years and 56-65 years, married, are housewives, and have an income of > Rp. 6,000,000. Consumption of organic vegetables is done erratically. Health and environmental sustainability are aspects that consumers consider in buying organic vegetables. Most consumers get information about organic vegetables from electronic media. Product quality, especially product freshness, is the main focus in finding information and considerations when buying products. Consumers are satisfied with the product and will continue to buy organic vegetables at Warung Sehat 1000 Kebun Bandung even though there is an increase in prices. The development of information and communication technology, income, lifestyle, and knowledge are the main considerations for consumers in buying organic vegetables. The family is the main reference for consumers in purchasing organic vegetables. Most of the purchases of organic vegetables are made by consumers at the instigation of themselves.